Sinergi Regional ASEAN dalam Mengatasi Tantangan Over Tourism - Ningsih, Walda Okvi Juliana; Sari, Dewi Fortuna (Global and Policy Journal of International Relations, 2024)
ABSTRACT Over tourism is one of the main challenges in the Southeast Asian region that can damage the environment, threaten the sustainability of local culture, and reduce the quality of life of local communities. This study aims to analyze and develop a roadmap for ASEAN regional synergy in overcoming over tourism through innovative and sustainable strategies. Using explanatory methods and qualitative approaches, this study examines ASEAN synergy through the implementation of The Action Roadmap for Sustainable Tourism Development ASEAN and the framework of the UN World Tourism Organization. The results of the study indicate that wise destination management, diversification of tourist locations, and improvement of environmentally friendly infrastructure are the main strategies to reduce the impact of over tourism. In addition, cross-sector collaboration between the government, private sector, and local communities is considered very important for the successful implementation of this strategy. Increasing tourist awareness and systematic measurement and evaluation are also keys to success in maintaining the sustainability of tourism in the ASEAN region. Keywords: Over Tourism, Sustainable Tourism, ASEAN, Regional Synergy, Destination Management ABSTRAK Over tourism merupakan salah satu tantangan utama di kawasan Asia Tenggara yang dapat merusak lingkungan, mengancam keberlanjutan budaya lokal, dan menurunkan kualitas hidup masyarakat setempat. Penelitian ini bertujuan untuk menganalisis dan mengembangkan peta jalan sinergi regional ASEAN dalam mengatasi over tourism melalui strategi yang inovatif dan berkelanjutan. Dengan menggunakan metode eksplanatif dan pendekatan kualitatif, penelitian ini mengkaji sinergi ASEAN melalui mplementasi The Action Roadmap for Sustainable Tourism Development ASEAN serta kerangka kerja dari UN World Tourism Organization. Hasil penelitian menunjukkan bahwa pengelolaan destinasi yang bijaksana, diversifikasi lokasi wisata, dan peningkatan infrastruktur ramah lingkungan menjadi strategi utama untuk mengurangi dampak over tourism. Selain itu, kolaborasi lintas sektor antara pemerintah, sektor swasta, dan masyarakat lokal dinilai sangat penting untuk keberhasilan implementasi strategi ini. Peningkatan kesadaran wisatawan serta pengukuran dan evaluasi yang sistematis juga menjadi kunci keberhasilan dalam menjaga keberlanjutan pariwisata di kawasan ASEAN. Kata Kunci: Over Tourism, Pariwisata Berkelanjutan, ASEAN, Sinergi Regional, Pengelolaan Destinasi